Strategy Of The Ministry Of Pariwista Timor-Leste In The Development Of Community Based Pariwista - Bernabe De Lima Araujo (CV. Ulil Albab Corp, 2024)
The Timor-Leste government's strategy in building a community-based pariwista sector “this study aims to find out and analyze the Timor-Leste government's strategy in building the community tourism sector, and what phenomena the Government faces in building a community-based tourism sector, by describing the results of the local government's strategy in building a community-based tourism sector. Based on data and information, the ministry of tourism has always tried to build a pariwista sector for the nation and the State, despite the many obstacles or obstacles faced by the ministry, but the government through the Ministry of Tourism of Timor-Leste remains steadfast in the combination or Matadalan